Interactive Effects of Microplastics and Tetracycline on Bioaccumulation and Biochemical Status in Jian Carp (Cyprinus carpio var. Jian) - Zhang, Chaonan; Wang, Qiujie; Zuo, Zhiheng; Ding, Jianhua; Xu, Guohuan; Zou, Jixing (Frontiers in Environmental Science, 2021)
Microplastics (MPs) and tetracycline (TC) are severe emerging pollutants in the aquatic environment. But there is a lack of research to investigate the interactive effects of MPs and TC in vivo. This study used Jian carp (Cyprinus carpio var. Jian) as the model organism to explore the bioaccumulation and biochemical status when exposed to MPs and TC, alone and combined. The accumulation of TC and MPs in intestine, variation of enzyme activities in intestine, and expression of immune-related genes in muscle were evaluated. Our results found the bioaccumulation of MPs was not affected by TC, but the presence of MPs would change the content of TC within 48 h. The SOD and LDH activity showed that TC-MPs combined exposure could reduce oxidative damage to Jian carps compared to MPs exposure alone. The IBR index showed SOD activity was sensitive to TC-MPs exposure. In addition, co-exposure to MPs and TC could alleviate the overexpression of IL-1β, IL-10, TGF-β, and TLR-2 induced by TC in muscles. TLR-2 gene has the potential to be the candidate gene reflecting the injury of TC exposure. In conclusion, it is inferred that co-exposure may reduce the toxicity of individual exposure in the living organisms. This study provides essential information for the risk assessment of pollution with MPs and TC, individually and combined, as well as a foundation to investigate the interactive effects of MPs and antibiotics on aquatic ecosystems.